Effectiveness of compassion-focused therapy on psychological distress and fear of negative evaluation in married women of Isfahan city - Hayatifar, Zhila; Iravani, Mohamadreza (Psychology of Woman Journal, 2022)
This study aimed to investigate the training of compassion-focused therapy on psychological distress and fear of negative evaluation in married women. The current research method was quasi-experimental with a pre-test and post-test design with a control group. The statistical population of this research was women aged 20 to 45 years who were referred to psychological counseling and services centers under the supervision of the Isfahan welfare organization in 1400 due to marital problems and conflicts. Thirty female clients who had this problem based on the marital conflicts questionnaire of Sanaei, Barati, and Bustanipour (2008) were included in the study according to available sampling, and randomly, 15 people were placed in the experimental group, and 15 people were in the control group. Data collection tools were Sanai et al.'s Marital Conflicts Questionnaire, Leary's Fear of Negative Evaluation Scale, and Kessler's Psychological Distress Questionnaire. Data analysis was done using SPSS version 26 software. In this research, multivariate analysis of covariance (MANCOVA) was used to analyze the obtained data, check all hypotheses, determine the intervention's effect on the experimental group, and evaluate the difference in the scores of the two groups in the pre-test and post-test intervals. The results obtained from the research indicate that compassion-focused treatment training affects psychological distress and fear of negative evaluation in married women.